Comparison of Hens Reared in Free-Range and Deep-Litter Systems in Terms of Certain Production Characteristics - İsmail Türker; Sezai Alkan (Journal of Agricultural Sciences)
The study was carried out compare the hens reared in free range system and deep-litter system in terms of certain production characteristics. A total of 300 Lohmann Brown hens, with 150 hens in each of the groups were used in the study. In the free range system, 4 m2 grazing ground was allocated for each hen. The hens were taken into research henhouse at 16 weeks of age and production characteristics were determined up to 52 weeks of age. It was determined that out of the characteristics focused in the study, there is no significant difference between the groups in terms of viability, 50% production age, egg weight, hen-day egg production, feed efficiency, feed consumption and body weight at 18 week of age, whereas there is a significant difference in terms of final body weight. In the study, it was concluded that hens in the deep-litter system gained more body weight compared to those in the free-range system but the other characteristics were not affected by the husbandry systems.